Involvement of Wnt Signaling in Dermal Fibroblasts - Kabashima, Kenji (American Society for Investigative Pathology, 2010)
Pachydermoperiostosis (PDP) is a rare disease characterized by unique phenotypes of the skin and bone, such as thick skin, implying that it may be caused by dysregulation of mesenchymal cells. The aim of this study is to examine the roles of dermal fibroblasts in the pathogenesis of pachydermia in association with Wnt signaling. The numbers of cultured fibroblasts were compared between healthy donors and PDP patients, and mRNA expression profiles in cultured dermal fibroblasts were examined by DNA microarray analysis and real-time reverse transcription-PCR. DKK1 and β-catenin protein expressions were also evaluated by immunohistochemistry in the skin. To evaluate the in vivo roles of DKK1 in mice, DKK1 small interfering RNA was injected to the ears. We found that PDP fibroblasts proliferated more than control fibroblasts and that mRNA expression of a Wnt signaling antagonist, DKK1, was much lower in PDP fibroblasts than in normal ones. Consistently, decreased expression of DKK1 in fibroblasts and enhanced expression of β-catenin were noted in PDP patients. Moreover, recombinant human DKK1 protein decreased the proliferation of dermal fibroblasts. In accord with the above human studies, intradermal injections of DKK1 small interfering RNA into mouse ears increased ear thickness as seen in PDP. Our findings suggest that enhanced Wnt signaling contributes to the development of pachydermia by enhancing dermal fibroblast functions.